Chemical composition and antimicrobial activity of berry essential oil of Juniperus oxycedrus L. (Cupressaceae) grown wild in Republic of Macedonia - Floresha Sela; Marija Karapandzova; Gjose Stefkov; Ivana Cvetkovikj; Elena Trajkovska-Dokikj; Ana Kaftandzieva; Svetlana Kulevanova (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2013)
Chemical composition and antimicrobial activity of essential oil isolated from berries from 2 different samples of Juniperus oxycedrus L. (Cupressaceae), growing wild in Republic of Macedonia was investigated. Performing GC/FID/MS analysis, one hundred components were identified, representing 96.0-98.95% of the oil. The major components were α-pinene (22.54- 27.12%), myrcene (11.26- 15.13%) and limonene (2.78-18.06%). Antimicrobial screening of the J. oxycedrus essential oils was made by disc diffusion and broth dilution method against 16 bacterial isolates of Gram positive and Gram negative bacteria and one strain of Candida albicans. The most sensitive bacteria was Haemophilus influenzae (MIC = 125 ml/ml). The essential oils showed moderate antimicrobial activity against Streptococcus pneumoniae, Staphylococcus aureus, Streptococcus agalactiae, Streptococcus pyogenes, Corynebacterium spp., Escherichia coli and Campilobacter jejuni (MIC > 500 ml/ml) and no activity against Candida albicans, Staphylococcus epidermidis, Acinetobacter spp., Salmonella enteritidis, Shigella flexnery, Klebsiella pneumonia, Pseudomonas aeruginosa, Enterococcus and Proteus mirabilis.